Estudo do mecanismo de ação antinociceptivo da Persea americana Mill - CASTRO, Tázia Lopes de (2020)
According to the International Association for the Study of Pain, pain is defined as “an unpleasant sensory and emotional experience associated with real or potential tissue damage, or described in terms of such injuries” and therapeutic alternatives are increasingly sought for their management. In view of the amount of properties and constituents present in Persea americana Mill., it becomes the target of experimental studies in order to validate the information about the species in its popular use, having in the literature studies that describe anti-inflammatory and analgesic properties of the extract watery of its leaves. The aim of the study was to investigate the possible mechanisms involved in the antinociceptive action of the ethyl acetate (F.PaAcet) and butanolic (F.PaBut) fraction of the plant species. The participation of the opioid pathway, L-arginine-nitric oxide, α-adrenoreceptors and muscarinic system in the antinociceptive and anti-inflammatory activity of the fractions was evaluated through the formalin-induced nociception test and carrageenan paw edema. F.PaAcet and F.PaBut showed significant anti-inflammatory action in the tested doses and concentrations. In the formalin test, when evaluating the opioid pathway, only the positive control group (CP) showed a statistically significant difference (p <0.05) in the licking time in the inflammatory phase, when compared to the other groups. In the LNAME- Nitric Oxide pathway, the CP and F.PaBut group showed a statistically significant difference (p <0.05) in the licking time in the inflammatory phase, when compared to the others groups. In the α-2 adrenergic pathway, F.PaBut showed a statistically significant difference (p <0.05) in the licking time in the inflammatory phase, when compared to the other groups. In the paw edema test, F.PaBut was able to reduce the edema in 60 and 120 minutes, when evaluating the participation of the Larginine- nitric oxide pathway and only in 240 minutes when evaluating the a-2- adrenergic pathway. F.PaAcet reduced edema from 60 minutes until the end of the test, when evaluating the participation of the L-arginine-nitric oxide pathway and only in 240 minutes when evaluating the alpha-2-adrenergic pathway. It’s suggested that the fractions have their activities associated with the modulation of NO release, as well as the modulation of the release of noradrenaline from the sympathetic terminals in the inflammatory phase of the formalin-induced nociception test and carrageenan-induced paw edema, associated with inhibition of release of inflammatory mediators, such as histamines, serotonin, bradykinin and prostaglandins, indicating a potential use of the plant species in the preparation of drugs for the treatment of inflammatory diseases.